The golden ratio in the pulmonary circulation in patients with heart failure and cardiogenic shock - Hoong Sern Lim; Ivan H. W. Yim (Physiological Reports)
Abstract The consistent relationship between pulmonary artery systolic (PASP), diastolic (PADP), mean (mPAP), and pulse (PP) pressures has led to the proposal of the golden ratio (Φ) hypothesis. This study tested the Φ hypothesis in the pulmonary circulation of patients with advanced heart failure (HF) and cardiogenic shock (CS). PASP:mPAP, mPAP:PADP, and PP:mPAP ratios were evaluated in 20 patients with advanced HF (high‐fidelity measurements) and 93 patients with CS (fluid‐filled system). Twelve of 20 patients with advanced HF had PASP:mPAP and mPAP:PADP ratios from high‐fidelity measurements that were consistent with the Φ hypothesis. The eight patients with low PASP:mPAP and mPAP:PADP ratios had lower PP: mPAP ratio (0.72 (0.71–0.73) vs. 0.94 (0.92–0.99), p = 0.002). In patients with CS, 76 patients (82%) had PASP:mPAP and mPAP:PADP ratios that were consistent with the Φ hypothesis. The 17 patients with CS and “low ratios” also had lower PP:mPAP (0.53 (0.48–0.57) vs. 0.74 (0.68–0.87), p < 0.001). Lower PP:mPAP ratio was related to higher filling pressures and lower cardiac power output. The pulmonary circulation deviated from the Φ hypothesis in patients with more severe HF and CS. Low PP:mPAP ratio identifies patients with HF and CS with more severe hemodynamic compromise.